2016
DOI: 10.1177/2165079916630552
|View full text |Cite
|
Sign up to set email alerts
|

Do Personal Factors or Types of Physical Tasks Predict Workplace Injury?

Abstract: Occupational health research has shown that certain worker and job characteristics are risk factors for workplace injuries. Workers who engage in physically demanding jobs, especially those jobs that involve repetitive motion, are at greater risk for work-related musculoskeletal disorders (WMSD). These risks are particularly prevalent in the health care sector. It is often reported that nurses are at higher risk of workplace musculoskeletal injury than other health care workers due to frequent lifting and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
1
13
1
2
Order By: Relevance
“…The prediction accuracy of any such model is highly specific for population characteristics (e.g., gender, age group, activity) and context (e.g., environment, task). Significant differences in physical demands and worker characteristics among occupational settings could be responsible for the contradictory findings of studies conducted to identify risk factors for work‐related musculoskeletal injury (Oranye et al., ). The purpose of this study is simply to demonstrate an alternative approach to the majority of human movement research that has reported averaged values for groups (Hug & Tucker, ).…”
Section: Developing Injury Risk Models For Occupational Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prediction accuracy of any such model is highly specific for population characteristics (e.g., gender, age group, activity) and context (e.g., environment, task). Significant differences in physical demands and worker characteristics among occupational settings could be responsible for the contradictory findings of studies conducted to identify risk factors for work‐related musculoskeletal injury (Oranye et al., ). The purpose of this study is simply to demonstrate an alternative approach to the majority of human movement research that has reported averaged values for groups (Hug & Tucker, ).…”
Section: Developing Injury Risk Models For Occupational Settingsmentioning
confidence: 99%
“…There are similarities in certain types of injuries sustained by athletes and workforce population. For example, joint ligament sprains and muscle-tendon strains represent the most common injuries sustained by competitive athletes (Hootman, Dick, & Agel, 2007;Darrow, Collins, Yard, & Comstock, 2009), as well as workers whose jobs impose a high level of physical demand (Baragaba et al, 2016;Oranye et al, 2016). Both athletes and workers often sustain lower back injuries, which can result in persisting impairment of neuromuscular control mechanisms that increase susceptibility to both upper extremity and lower extremity musculoskeletal injuries (Nadler, Malanga, DePrince, Stitik, & Feinberg, 2000;Massé-Alarie, Beaulieu, Preuss, & Schneider, 2015).…”
Section: Developing Injury Risk Models For Occupational Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, esses sintomas são resultantes de vários fatores que podem predispor os trabalhadores às lesões musculoesqueléticas, incluindo políticas e práticas organizacionais, fatores predisponentes presentes no ambiente de trabalho, das características do trabalhador e do grupo ocupacional a que pertence (Orange et al, 2016).…”
Section: Introductionunclassified
“…Assim, os fatores mencionados, os fatores biomecânicos e os psicossociais são os principais agentes motivadores (Orange et al, 2016;Alireza et al, 2020). Logo, são considerados os grandes preditores do surgimento de quadros álgicos nos DORT a movimentação manual, o trabalho repetitivo e o estático, as vibrações e as condições psicológicas e as sociais precárias entre trabalhadores expostos (Ministério da Saúde, 2019).…”
Section: Introductionunclassified